Pembelajaran Daring Interaktif menggunakan Flipbook dan Pengaruhnya terhadap Proses dan Hasil Blended Learning - Kalalo, Reva Johanna Princesa; Lumenta, Arie S.M.; Paturusi, Sary D. E. (Universitas Sam Ratulangi, 2021)
Abstract — The development of information and communication technology nowadays provides more accessibility for humans. Education has implemented a face-to-face model and an online learning model called Blended Learning which is an improvement of E-Learning Method. E-learning has allowed people to access learning materials in real time way from anywhere. Moreover, the learning material can be enhanced with various learning sources and updated by the teacher. Therefore, this research of Interactive Online Learning using a flipbook aims to identify the impact on the process and results of the blended learning. This research uses experimental methods and a pretest-posttest control class and experimental class designs, with the aim of knowing the effect of the flipbook on the Discrete Mathematics Class and the Computer System on student learning outcomes. The results of research conducted in the Discrete Mathematics Class show that student learning outcomes in the experimental class are better than those in the control class. Students in the experiment class scored higher with an average of 92.00, while those in the control class scored an average of 87.00. The results of research conducted in the Discrete Mathematics Class showed that student learning outcomes in the experimental class are better than those in the control class. Students in the experiment class get a higher average score of 93.00 while those in the control class get an average score of 85.00. Based on the results of the two courses, it shows that the experimental class has more influence on Blended Learning. Keywords — Blended Learning; E-Learning; Experimental Research; Flipbook; Interactive. Abstrak — Perkembangan teknologi informasi dan komunikasi pada saat ini semakin memberikan kemudahan kepada manusia. pendidikan telah menerapkan model tatap muka dan model pembelajaran daring disebut Pembelajaran Campuran yang merupakan penyempurnaan Metode E-Learning. Melalui E-learning materi pembelajaran dapat diakses kapan saja dan dari mana saja, disamping itu materi yang dapat diperkaya dengan berbagai sumber belajar dan dapat diperbaharui oleh pengajar. Dirancanglah Pembelajaran Daring Interaktif menggunakan Flipbook dan Pengaruhnya terhadap proses dan hasil Blended Learning. Penelitian ini menggunakan Metode Eksperimental. Desain yang digunakan dalam penelitian ini adalah Pre Test Post Test Kelas Kontrol dan Kelas Eksperimen, dengan tujuan untuk mengetahui pengaruh Flipbook pada Kelas Matematika Diskrit dan Sistem Komputer terhadap hasil belajar mahasiswa. Hasil penelitian pada Kelas Matematika Diskrit menunjukkan hasil belajar pada kelas eksperimen berpengaruh dari pada hasil belajar pada kelas kontrol. Mahasiswa di Kelas Eksperimen mendapatkan nilai yang lebih tinggi dengan rata-rata 92.00 dan untuk Mahasiswa di Kelas Kontrol mendapatkan nilai dengan rata-rata 87.00. Hasil penelitian yang dilakukan pada Kelas Matematika Diskrit menunjukkan hasil belajar mahasiswa pada kelas eksperimen lebih berpengaruh daripada hasil belajar pada kelas kontrol. Mahasiswa Kelas Eksperimen mendapatkan nilai yang lebih tinggi dengan rata-rata 93.00 dan untuk mahasiswa kelas Kontrol mendapatkan nilai dengan rata-rata 85.00. Berdasarkan hasil dari kedua mata kuliah menunjukkan bahwa kelas eksperimen lebih berpengaruh terhadap Blended Learning. Kata kunci — Blended Learning; E-Learning; Penelitian Eksperimental; Flipbook; Interaktif.